Polyphenol-Protein Complexes and Their Consequences for the Redox Activity, Structure and Function of Honey. A Current View and New Hypothesis – a Review - Brudzynski Katrina; Maldonado-Alvarez Liset (Polish Journal of Food and Nutrition Sciences)
There is increasing evidence that protein complexation by honey polyphenols is changing honey structure and function. This relatively less investigated filed of honey research is presented in a context of known mechanism of formation of the stable polyphenol-protein complexes in other foods. At a core of these interactions lies the ability of polyphenols to form non-covalent and covalent bonds with proteins leading to transient and/or irreversible complexes, respectively. Honey storage and thermal processing induces non-enzymatic oxidation of polyphenols to reactive quinones and enables them to form covalent bonds with proteins. In this short review, we present data from our laboratory on previously unrecognized types of protein-polyphenol complexes that differed in size, stoichiometry, and antioxidant capacities, and the implications they have to honey antioxidant and antibacterial activities. Our intent is to provide a current understanding of protein-polyphenol complexation in honey and also some new thoughts /hypotheses that can be useful in directing future research.